State influence on the formation of legal culture under martial law: the experience of Ukraine - Viktoriia Polishchuk; Olena Chomakhashvili; Kateryna Shvets; Ivan Hafych; Olena Nadiienko (Qubahan Academic Journal)
The rapid development of information technologies, which has invaded absolutely all spheres of social life, dictates its own rules and imposes strict requirements on every person. At the current stage of the development of society, in the era of globalization, it is undoubtedly important to understand the significance and correctness of conducting state policy, making strategic decisions, the development of influential spheres of state management that are of primary importance for the prosperity of the country, awareness of making expected decisions or, on the contrary, the expediency of making unpredictable behavioral strategies. Under the conditions of a full-scale invasion of a neighboring state on the territory of Ukraine, an understanding of the reasons for military aggression against Ukraine, opposition to a totalitarian regime, injustice and the struggle for independence is formed. Such factors definitely affect the general formation of the legal culture of the population of Ukraine. The purpose of the article is to study the directions of the development of the legal culture of the population in Ukraine and beyond, to identify those phenomena that have an impact on the legal education of the population and, based on them, to formulate the most successful and effective development vectors for increasing the role of the legal culture of the population in the conditions of martial law in Ukraine. Such knowledge is of particular interest, because it makes it possible to develop a strategy for reducing the level of crime in the state by improving the legal culture of the population.